Analisis kesalahan sintaksis bahasa Indonesia dalam karangan narasi siswa kelas V sekolah dasar - Aulia Rahmawati; Slamet Slamet; Anesa Surya (Universitas Sebelas Maret, 2022)
Abstract. This study aims to describe syntactic errors in the fields of phrases, clauses, and sentences. Describe the factors that cause syntactic errors in narrative essays for fifth grade students of SD Negeri Tegalayu Surakarta. This study uses a qualitative method. Methods of data collection is done by means of interviews, observation and documentation. The validity of the data using triangulation techniques and sources. Analysis of the data using the interactive model of Miles and Huberman. The results of the research based on indicators in the phrase field contained errors, namely the use of regional languages, inappropriate prepositions, wrong wording, excessive elements, excessive superlative influences and the use of respiricals. The error of the clause is adding a preposition between the verb and the object. Sentence errors are unsubjected sentences, illogical sentences, ambiguous sentences, omission of conjunctions and the use of foreign terms. Internal and exte kurnal causes are lack of understanding of correct sentence structure, low reading interest, use of language in the surrounding environment. The implication of this research is that teachers must improve strategies to overcome syntax errors by explaining good and correct writing procedures according to syntax.Keywords: language error analysis, syntax, narrative essay